TRANSFORMASI DAKWAH DI ERA DIGITAL: PERAN MEDIA SOSIAL SEBAGAI PLATFORM SYIAR ISLAM - wali, Muhammad Wali Al-Khalidi; Yusfriadi (AT-TAWASUL, 2024)
The transformation of Islamic preaching in the digital age is inevitable in response to changes in communication patterns among the Muslim community. Social media has emerged as a highly promising new space for disseminating Islamic messages more widely, quickly, and interactively. This article aims to analyse how social media can be optimised as a platform for Islamic preaching, as well as the challenges and opportunities faced by preachers in the digital space. Using a descriptive-qualitative approach through literature review, this article reveals that the success of digital da'wah is highly dependent on content creativity, understanding of social media algorithms, and the moral integrity of da'is. The conclusion of this study emphasises the need to strengthen digital literacy, Islamic communication ethics, and cross-platform da'wah collaboration so